Complete mitochondrial genome of Diptychus maculatus (Cypriniformes: Cyprinidae: Schizothoracinae). (3rd May 2016) - Yang, Tianyan; Meng, Wei; Gao, Tianxiang; Hai, Sa; Guo, Yan
Abstact: The complete mitogenome sequence of the mitochondrial genome of Diptychus maculatus was amplified and analyzed in this study. It was 16, 895 bp in length and contained 13 protein-coding genes, 2 ribosomal RNA genes, 22 tRNA and 1 control region. Most of the genes were encoded on the heavy strand except for eight tRNA genes and DN6. The overall base composition of the complete mtDNA was 27.80% A, 26.70% T, 19.01% G and 26.49% C. A 312 bp-long sequence containing a tandem repeat array (37 bp) was found between tRNA Thr and tRNA Pro .